The efficacy and potential mechanism of cnidium lactone to inhibit osteoclast differentiation - Jun-Yang Liang; Wen-Liang Wu; Yun-Xia Chen; Haichun Liu (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Cnidium lactone is effective in the maintenance of bone mass in various osteoporosis models; however, the precise molecular mechanisms are not understood. In this study, we investigated the effects and underlying mechanisms of action of cnidium lactone on receptor activator of NF-κB ligand (RANKL)-induced osteoclastogenesis. Cnidium lactone dose-dependently inhibited osteoclast differentiation and formation, decreased the bone-resorbing activity of osteoclasts, and downregulated the expression of osteoclast differentiation marker genes. Cnidium lactone treatment considerably reduced RANKL-induced p38 MAPK and PI3K-Akt signal activity in RAW264.7 cells. The cnidium lactone-induced osteoclastogenesis was significantly attenuated by inhibition of p38 and PI3K through pretreatment with SB203580 and LY294002, respectively. Furthermore, cnidium lactone inhibited the expression of c-Fos and NFATc-1 with dose-dependently and enhanced by SB203580 and LY294002. In conclusion, cnidium lactone inhibits osteoclast differentiation through p38 MAPK and PI3K-Akt signalling pathway/c-Fos/NFATc1 signalling pathway.